Some surprising facts about working time accounts and the business cycle - Almut Balleer; Britta Gehrke; Christian Merkl (Kiel Institute for the World Economy (IfW), 2014)
This paper reveals that German firms with working time accounts (WTAs) show a similar separation and hiring behavior in response to revenue changes as firms without WTAs. This finding casts doubt on the popular hypothesis that WTAs were the key driver of the unusually small increase in German unemployment in the Great Recession. One possible explanation is that firms substitute WTAs by short-time work. However, our results show no evidence for this substitution. Firms with WTAs use short-time work more to adjust labor over the cycle than firms without WTAs.
Keywords: E20; E24; J20; J30; 330; working time accounts; short-time work; business cycle